Aktivitas Hepatoprotektor Ekstrak Metanol Akar Pasak Bumi dan Fraksi-Fraksi Turunannya - Panjaitan, Ruqiah Ganda Putri; Manalu, Wasmen; Handharyani, Ekowati; -, Chairul (Jurnal Veteriner; Vol 12 No 4 (2011), 2012)
The hepatoprotector activity of pasak bumi (Eurycoma longifolia Jack.) roots was evaluated in carbontetrachloride (CCl4)-induced rats. Each rat was administered 500 mg/kg body weight of metanol extractand its derivates (n-hexane, chloroform, ethyl acetate, and methanol-water) for 7 consecutive days. Thepositive control group received 25 mg silymarin/kg body weight daily for 7 consecutive days. Hepatoprotectoractivity was assessed by measuring serum alanine transaminase (ALT) and aspartate transaminase(AST). Futhermore, hepatic tissues were subjected to histopathological studies. The results and AST(272.33±85.63 U/L) compared to methanol extract (380.61±324.88 U/L and 475.27±412.31 U/L), n-hexanefraction (279.80±304.92 U/L and 488.53±426.81 U/L), chloroform fraction (418.30±294.80 U/L and427.70±273.08 U/L), and ethyl acetate fraction (312.80±443.30 U/L and 418.40±370.52 U/L), but thisresult was not as good as silymarin (ALT 105.09±21.62 U/L and AST 310.25±2.45 U/L). Moreover, thehistopathological studies of methanol-water fraction was also not as good as silymarin . It was concludedthat methanol-water fraction of pasak bumi roots has a hepatoprotector potensial.
Keywords: Eurycoma longifolia Jack.,CCl4, hepatoprotector